Análises microbiológicas e quantificação de proteína de soja pela metodologia isotópica (δ13C and δ15N) em hambúrgueres bovinos de marcas comerciais brasileiras - Ducatti, Rhani [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The burger is a manufactured meat product and potential vehicle of bacteria producers or not of toxins in various stages of processing, from its origin to the stage of transformation, storage, transport and distribution to consumption. Moreover, their composition requirements are susceptible to fraud by excessive use of protein extenders. These ingredients help in reducing the cost of formulation of the final products and maximize profits of fraudulent industries. The supervisory agencies monitoring is hindered by the lack of appropriate analytical methodologies. Within this context, it is necessary to evaluate the hygienic- sanitary aspects of burgers through microbiological analysis and the determination and quantification of soy protein. Were analyzed 110 samples of beef hamburgers of 11 brazilian trademarks by the technique of stable isotopes of Nitrogen-15 and Carbon -13 and second microbiological methodology described by Normative Instruction n° 62 of August 26, 2003. All 11 brazilian trademarks presented bacterial counts within the limit (5x103 CFU/g) for coliforms at 45°C , while the values for Staphylococcus coagulase positive were above the allowed patterns (5x103 CFU/g) in brands H (samples 1 and 7). Brands B (sample 5) , D (sample 5) , E (sample 5) and G (sample 4) also had scores above the stipulated (3x103 CFU/g) for Clostridium sulphite reducing to 46°C and sample 6 of brand L was positive for Salmonella spp. Only 3 samples of G brand were within 4% addition of non-meat protein stipulated by IN 20 07/31/2000. All other 107 samples from 11 trademarks cheated the specific legislation

O hambúrguer é um produto cárneo industrializado e potencial veículo de bactérias produtoras ou não de toxinas nas diversas fases de seu processamento, desde sua origem até as fases de transformação, armazenagem, transporte e distribuição para o consumo. Além disso, seus requisitos de composição são susceptíveis à fraude pelo uso excessivo de extensores protéicos. Estes ingredientes auxiliam na diminuição nos custos de formulação dos produtos finais e maximizam os lucros de indústrias fraudulentas. A fiscalização pelos órgãos de vigilância é dificultada pela carência de metodologias analíticas apropriadas. Dentro deste contexto, tornase necessária a avaliação do aspecto higiênico-sanitário dos hambúrgueres através das análises microbiológicas e a determinação e quantificação da proteína de soja. Foram analisadas 110 amostras de hambúrgueres de carne bovina de 11 marcas comerciais brasileiras através da técnica dos isótopos estáveis de Nitrogênio -15 e Carbono-13 e segundo a metodologia microbiológica descrita pela Instrução Normativa n° 62 de 26 de agosto de 2003. Todas as 11 marcas comerciais brasileiras apresentaram contagem bacteriana dentro do limite (5x103 UFC/g) para Coliformes a 45°C, enquanto os valores para Staphylococcus coagulase positiva estavam acima dos padrões permitidos (5x103 UFC/g) na marca H (amostras 1 e 7). As marcas B (amostra 5), D (amostra 5), E (amostra 5) e G (amostra 4) também apresentaram contagens acima do estipulado (3x103 UFC/g) para Clostridium sulfito redutor a 46°C e a amostra 6 da marca L foi positiva para Salmonella spp. Apenas 3 amostras da marca G encontraram-se dentro dos 4% de adição de proteína não cárnica estipulados pela IN n° 20 de 31/07/2000. Todas as outras 107 amostras das 11 marcas comerciais burlaram a legislação específica em vigor
Microbiological analysis and quantification of soy protein using the isope method (δ13C and δ15N) for commercial of beef hamburger
Keywords: Alimentos de origem animal - Adulteração e inspeção; Carne bovina - Contaminação; Carne - Inspeção; Isótopos estáveis; Microbiologia; Vigilância sanitária; Meat inspection; Stable isotopes